PENGEMBANGAN BIOGAS SAMPAH PASAR - Budi Nining Widarti; Gadis Dilasari; Edhi Sarwono (Universitas Lambung Mangkurat, 2022)
The traditional market has degradable waste, especially from the types of vegetables and left over food, the waste is not managed properly will potentially cause disease and poor aesthetics. There are various kinds of recycling and waste utilization efforts to reduce the potential negative impacts and produce a product that is more economically valuable so that the volume of waste does not continue to increase. Based on this consideration, it is necessary to study the generation and composition of waste as well as the potential for biogas from waste in Pasar Pagi Samarinda. The organic material of Pasar Pagi waste which is used as energy through the anaerobic digestion process can be considered from the quality of the biogas and the volume of biogas produced. The determination of waste generation and volume of waste is calculated based on the number of traders in the Pasar Pagi. The biogas production in the digester uses organic waste raw materials from Pasar Pagi and rumen liquid in a ratio of 1:1. The Calculation of gas formed was carried out using a U manometer, temperature measurements using a thermometer, pH measurements using a pH meter were carried out every day and VS measurements were carried out every seven days. The mass of Pasar Pagi waste was 1.81 kg/trader/day and for the volume unit is 4.90 L/trader/day. The total composition of organic waste for vegetables, fruit, and food waste was 85.5%, organic waste in the form of cardboard or paper waste was 2.9%, the composition of plastic waste was 10.7% and metal was 0.9%. The pH of the digester during the formation of biogas shows an acidic condition, and the increase in pH that occurs is only able to reach pH 6 or close to neutral. The temperature in the digester at the beginning of the process tends to increase, then decreases and increases again at the end of the process, but does not affect the biogas production that is still ongoing. The addition of cow rumen contents was able to increase the volume of biogas formed in organic matter and the VS value decreased every week accompanied by the increase in biogas production. This shows that the organic waste in Pasar Pagi has the potential for biogas production.